1974
DOI: 10.1111/j.1432-1033.1974.tb03731.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Phosphatidylcholine between Liposomes

Abstract: Liposomes of sufficiently different surface charge can be separated on a DEAE-cellulose column. This made possible the present study on the transfer of phosphatidylcholine between liposomes consisting of phosphatidylcholine and various amounts of phosphatidic acid. It was demonstrated that the redistribution of ['4C]phosphatidylcholine between liposomes as catalyzed by the phosphatidylcholine exchange protein, followed the kinetics of an isotope-exchange reaction. Furthermore, it was shown that the phospholipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…3). A similar observation has been made for sphingomyelin [2]. This demonstrates that in addition to the membrane surface charge other factors may regulate the activity of the exchange protein.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…3). A similar observation has been made for sphingomyelin [2]. This demonstrates that in addition to the membrane surface charge other factors may regulate the activity of the exchange protein.…”
Section: Discussionsupporting
confidence: 57%
“…It is presumably by this mechanism that in the present study the protein transfers ['4C]phosphatidylcholine from the 14C-labelled mitochondria to the liposomes. Previously in studying the transfer of phosphatidylcholine between single bilayer liposomes, it was demonstrated that the transfer decreased with an increase of negatively charged phosphatidic acid in the liposomes [2,3]. An analysis of the kinetic data indicated that the apparent dissociation constant of the exchange protein-liposome complex decreased in a parallel fashion resulting in an inhibition of transfer [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incubations of erythrocytes with lipid vesicles in the absence of exchange protein and incubations with exchange protein but without lipid vesicles showed that under these conditions erythrocytes stayed intact, maintained their original shape and appeared to have unaltered phospholipid compositions. In addition extensive studies on the properties of the purified exchange protein as used in our experiments have shown that this protein has no detectable proteolytic or other enzymatic functions but act solely as a phosphatidylcholinespecificcarrier [7][8][9][10][11][12][13]15,17,18]. Analysis of erythrocyte phosphatidylcholine at this extent of exchange (25 % replacement) was performed by both thin-layer and gas-liquid chromatography (Table 1).…”
Section: Incorporution Of Dipalmitoylglycerophosplzocholitwmentioning
confidence: 99%
“…In this regard the introduction of exchange proteins [l-41 offers the opportunity to conservatively alter the membrane structure in a systematic fashion. Thus far, phosphatidylcholineexchange proteins have been shown to function between various donor-acceptor pairs ; mitochondria with microsomes [5 -71, microsomes with liposomes [8], liposomes with liposomes [9] and erythrocyte ghosts with vesicles [lo] and liposomes [ll]. Recently van Meer et al [12,13] demonstrated the exchange of phosphatidylcholine between intact human and rat erythrocytes and various donor systems such as microsomes, liposomes, vesicles and etherosomes.…”
mentioning
confidence: 99%